Association of Haemophilia with Down Syndrome - Narang, Gursharan Singh; Singh, Tarsem; Sharma, Anubha; Malik, Supriya; Kaur, Amandeep (Journal of Nepal Paediatric Society, 2016)
Hemophilia B is a hereditary bleeding disorder caused by a lack of blood clotting factor IX. Without enough factor IX, the blood cannot clot properly to control bleeding. Hemophilia B presenting in association with Down’s syndrome is quite rare. We report a case of a one month old child who presented to us with continuous unexplained bleeding. J Nepal Paediatr Soc 2016;36(1):75-77.